Relasi Islam dan Budaya Lokal di Kalimantan Timur: Persepsi Tokoh Masyarakat Mengenai Islam Nusantara - Noorthaibah, Noorthaibah; Rozak, Abdur - (Jurnal Kawistara, 2020)
Islam Nusantara gave rise to many perceptions in the midst of Indonesian Muslim society, both in terminological discourse and practical perception. This study presents the results of qualitative research on Islam Nusantara in the perception of East Kalimantan community leaders from the Regency of Paser Grogot, Kutai Kartanegara, Samarinda City and Berau. In their perception Islam Nusantara is perceived as a catalyst between Islam, nationality, plurality and eternal truth. This was stated in the form of understanding and practice by East Kalimantan community leaders in religious life. In terms of their understanding, Islam Nusantara is perceived as a functional instrument of mutualism between Islam and culture towards productive diversity. While in practice, Islam Nusantara is placed as a foothold or starting point in carrying out da'wah to realize the simplification Â of human relations and eternal truth